Hibiscus Rosa-Sinensis Leaf As Coagulant In Wastewater And Leachate Treatments - Awang, Nik Azimatolakma (2011)

(untitled)
Applications of natural macromolecular coagulants are having a bright future because of their abundant source, low price, multifunction and its biodegradibility as compared to conventional chemical-based coagulants. The use of extracts from Hibiscus rosa-sinensis leaves as coagulant has not been discussed in literature. This research determines water (HBaqs) and thioglycollic acid treated (HBpowd) extraction of carbohydrate coagulants from the leaves of Hibiscus rosa-sinensis, and examines its chemical characteristics (i.e. isoelectric point (IEP), molecular weight and Fourier Transform Infrared).